Wind Diesel Hybrid System with Pitch Angle Controller (International Journal of Innovative Research in Engineering & Management, 2023)
A wind diesel hybrid system is an  autonomous electricity generating system using wind  turbines with diesel generators to obtain a maximum  contribution by the intermittent wind resource to the total  power produced, while providing continuous high quality  electric power. The main goal is to control load frequency  and reduce fuel consumption enabling reduced system  operating costs and environmental impacts. Frequency  control in a power system is done to maintain an adequate  balance between the consumed and generated active  powers, so that the frequency remains within acceptable  limits around the nominal frequency. Load–frequency  control (LFC) is of importance in electric power system  design and operation. The objective of the LFC in an  interconnected power system is to maintain the frequency  of each area within limits and to keep tie-line power flows  within some pre-specified tolerances by adjusting the MW  outputs of the generators so as to accommodate fluctuating  load demands.
Keywords: Energy; Hybrid System; Load Frequency Control; Wind Diesel System; Simulation